2021
DOI: 10.2147/rmhp.s291876
|View full text |Cite
|
Sign up to set email alerts
|

Extended-Spectrum Beta-Lactamase-Producing Gram-Negative Bacteria on Healthcare Workers’ Mobile Phones: Evidence from Tikur Anbessa Specialized Hospital, Addis Ababa, Ethiopia

Abstract: Background: Mobile phones are widely used in hospital settings for different purposes. Mobile phones of healthcare workers (HCWs) could be colonized or harbor extendedspectrum beta-lactamase (ESBL) producing gram-negative bacteria and may act as source of infectious agents. The aim of this study was to determine the rate of extended-spectrum beta-lactamase-producing Gram-negative bacteria on mobile phones of healthcare workers, to assess their antimicrobial susceptibility patterns and associated factors. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 34 publications
0
15
0
4
Order By: Relevance
“…We descriptively explained the antimicrobial susceptibility and multidrug resistance of bacterial isolates using 14 studies [21, 22, 24, 25, 42–46, 53–56, 58]. According to an Ethiopian study, bacterial isolates had a greater rate of resistance to penicillin (84%), ampicillin (81%), and tetracycline (81%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We descriptively explained the antimicrobial susceptibility and multidrug resistance of bacterial isolates using 14 studies [21, 22, 24, 25, 42–46, 53–56, 58]. According to an Ethiopian study, bacterial isolates had a greater rate of resistance to penicillin (84%), ampicillin (81%), and tetracycline (81%).…”
Section: Resultsmentioning
confidence: 99%
“…Following the exclusion of 844 articles, a total of 87 full-text papers were verified for eligibility using the pre-determined criteria, with 64 articles being excluded. Finally, 23 articles [21][22][23][24][25][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] that satisfied the criteria were included in the meta-analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Galazzi A et al have reported that the isolation rate of MRSA was up to 17% in ICU [ 26 ]. Another study from Ethiopia showed that Gram-negative bacteria were isolated from 8.3% of HCWs’ mobile phones and 79.4% of the isolates were multidrug resistant [ 31 ]. Antibiotic-resistant bacteria are the most serious health risk for hospitalized patients [ 32 ].…”
Section: Discussionmentioning
confidence: 99%